The Role of Business Ethics in Increasing Customer Loyalty - Hermansyah, Farel Ruben (Universitas Bhayangkara Surabaya, 2025)
This research aims to determine and analyze the role of business ethics on increasing customer loyalty at MDS Jaya Buah Surabaya Fruit Shop. The sample in this study was 3 people as informants, namely employees and customers of the MDS Jaya Buah Surabaya Fruit Shop. The research method used is a descriptive research method with qualitative method analysis and data collection used is primary data in the form of interview observations. Secondary data obtained from this study is documentation. The data analysis technique used is the Miles and Huberman Interactive Model, data reduction, data presentation, drawing conclusions and verification. The results of the study indicate that the application of business ethics at the MDS Jaya Buah Surabaya Fruit Shop is good. The implementation of business ethics is carried out by committing to continue to carry out honest, fair and responsible business practices. The impact of the implementation of business ethics on customer loyalty at the MDS Jaya Buah Surabaya Fruit Shop is very significant. Customers feel satisfied with good, honest, fair and responsible service.